The recent advances of cancer associated fibroblasts in cancer progression and therapy - Wu, Chenxi; Gu, Jianmei; Gu, Hongbing; Zhang, XiaoXin; Zhang, Xu; Ji, Runbi (Frontiers in Oncology, 2022)
As an abundant component of tumor microenvironment, cancer-associated fibroblasts (CAFs) are heterogeneous cell populations that play important roles in tumor development, progression and therapeutic resistance. Multiple sources of cells can be recruited and educated to become CAFs, such as fibroblasts, mesenchymal stem cells and adipocytes, which may explain the phenotypic and functional heterogeneity of CAFs. It is widely believed that CAFs regulate tumor progression by remodeling extracellular matrix, promoting angiogenesis, and releasing soluble cytokines, making them a promising cancer therapy target. In this review, we discussed about the origin, subpopulation, and functional heterogeneity of CAFs, with particular attention to recent research advances and clinical therapeutic potential of CAFs in cancer.